Differential proteomics and functional research following gene therapy in a mouse model of Leber congenital amaurosis. - Qinxiang Zheng; Yueping Ren; Radouil Tzekov; Yuanping Zhang; Bo Chen; Jiangping Hou; Chunhui Zhao; Jiali Zhu; Ying Zhang; Xufeng Dai; Shan Ma; Jia Li; et al. (PLoS ONE)
Leber congenital amaurosis (LCA) is one of the most severe forms of inherited retinal degeneration and can be caused by mutations in at least 15 different genes. To clarify the proteomic differences in LCA eyes, a cohort of retinal degeneration 12 (rd12) mice, an LCA2 model caused by a mutation in the RPE65 gene, were injected subretinally with an AAV vector (scAAV5-smCBA-hRPE65) in one eye, while the contralateral eye served as a control. Proteomics were compared between untreated rd12 and normal control retinas on P14 and P21, and among treated and untreated rd12 retinas and control retinas on P42. Gene therapy in rd12 mice restored retinal function in treated eyes, which was demonstrated by electroretinography (ERG). Proteomic analysis successfully identified 39 proteins expressed differently among the 3 groups. The expression of 3 proteins involved in regulation of apoptosis and neuroptotection (alpha A crystallin, heat shock protein 70 and peroxiredoxin 6) were investigated further. Immunofluorescence, Western blot and real-time PCR confirmed the quantitative changes in their expression. Furthermore, cell culture studies suggested that peroxiredoxin 6 could act in an antioxidant role in rd12 mice. Our findings support the feasibility of gene therapy in LCA2 patients and support a role for alpha A crystallin, heat shock protein 70 and peroxiredoxin 6 in the pathogenetic mechanisms involved in LCA2 disease process.